Consumers' inferences: Self-deception and self-efficacy. Issue 3 (3rd July 2018) - Chebat, Jean-Charles
Abstract: The article reviews the inference-based processes consumers employ to choose from products and services offered in stores, under the constraints of both limited cognitive efforts and limited time. The author contends that these processes bring about both self-deception and self-efficacy. On the one hand, the simplified cognitive processes lead to suboptimal decisions. On the other hand, they allow consumers to make "satisficing" decisions in the sense of Simon (1956, 1990) which comforts them in making these a cognitive part of the shopping routine.